Bimbingan Pra Nikah Secara Daring Pada Masa Pandemi Covid-19 dalam Tinjauan Maqashid Al-Shari’ah - Yaffi Jananta Andriansyah; Aunur Rofiq; Suwandi (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2023)
At the end of 2019, the world is experiencing the Covid-19 pandemic, which spreads very quickly. The government made Various policies, such as the PSBB policy, study from home, work from home, and other social restrictions. This has an impact on family harmony. Because there were many layoffs during the pandemic, it was vulnerable to domestic violence due to economic and other problems. The solution to domestic violence is to hold pre-marital counseling for prospective brides; during the pandemic and carried out online. The research method used is the library research method, using a normative juridical approach. Data collection techniques used documentation and analysis using descriptive and content analysis methods. During a pandemic, people spend more time at home, so domestic violence often occurs. Another reason is that many people have been laid off and are experiencing economic difficulties. Pre-marital counseling during a pandemic is carried out online, the implementation time is shortened, and strict health protocols must be implemented.